HISTORY OF MARKETING COMMUNICATION OF CINEMA PRODUCTION IN THE EXHIBITION INDUSTRY IN JEMBER - Hartanto, Denny Antyo (JURNAL PAKARENA, 2023)
This research aims to document the history of cinema product communication for the sake of archiving the history of cinema in the city of Jember. In addition, it also aims to identify and identify the background of the problems that have resulted in the cinema industry in Jember experiencing the closure of operations, so that the problems faced by the local exhibition industry in Jember can be identified. In addition to knowing the history of the development of cinema in the city of Jember.This research focuses on the study of documenting artifacts from the communication process of cinema production in Jember City. Before the industrialization of film exhibitions which was dominated by the Cinema 21 Group and modern cinemas with the Cineplex concept as it is today, the city of Jember once had several local cinema buildings as public spaces to be able to communicate film products to the audience as a fulfillment of the entertainment needs of the Jember people. However, in the 1990s some cinema buildings are now just history. The existence of the cinema building has disappeared from the circulation of the film industry in the city of Jember. The methods used are descriptive qualitative research methods and historical or historical methods. The results of the study are in the form of findings about historical facts and the problems that lie behind the local cinema industry in Jember experiencing operational closures and no trace so that historical documentation and historiography interests or historical writing of local cinema developments in Jember are needed. There are several factors that are indicated to be the cause of the closing of cinemas in Jember, namely: (1) Jember people have experienced boredom with hot films that are often screened in cinemas, (2) The emergence of private TV channels in the 1990s, (3) The ease of obtaining pirated film VCDs and the proliferation of VCD Players in people's homes, (4) The decline in the quality of Indonesian films, and (5) The ease with which people get new films in internet cafes (internet cafes) before the advent of the era of social media such as youtube.